Menghadapi Persaingan Pasar dan Teknologi Produksi: Pergulatan Perajin Perhiasan Tradisional di Desa Celuk, Bali - I Ketut Sida Arsa; Ni Made Ary Widiastini; Putu Indah Rahmawati (Pusat Kajian Bali Universitas Udayana, 2020)
The presence of jewelry casting machines in Celuk Village, Gianyar, Bali has caused a struggle among craftsmen in fighting for their business and production interests. This study aims to uncover and analyze the struggle practices. Data collection is done through interviews, observations and document studies. Data were analyzed with practical theory, deconstruction, mechanical reproduction and other supporting theories used eclectically. The results showed that the struggle was carried out in various ways depend on the capital they owned. All parties build images as an effort to maintain their existence. Various kinds of displays, product certificates, and discourse are played as media in struggling for their respective interests to win the market competitions. The struggle of jewelers craftsmen in Celuk gives birth to various forms of power relations, there are those who rule and are controlled. Power in jewelry is largely determined by space, time, and the amount of capital ownership.Keywords: jewelry, Celuk Village, traditional craftsman, casting, market competition.